Minimizing the time and cost of production of transgenic alfalfa libraries using the highly efficient completely sequenced vector pPZP200BAR - Bottero, Ana Emilia; Pascuan, Cecilia Gabriela; Pagano, Elba Maria; Ayub, Nicolás Daniel; Soto, Gabriela Cinthia; Jozefkowicz, Cintia (2017)
Alfalfa is the most important forage legume worldwide. However, similar to other minor forage crops, it is usually harvested along with weeds, which decrease its nutrient quality and thus reduce its high value in the market. In addition, weeds reduce alfalfa yield by about 50 %. Although weeds are the limiting factor for alfalfa production, little progress has been made in the incorporation of herbicide-tolerant traits into commercial alfalfa. This is partially due to the high times and costs needed for the production of vast numbers of transgenic alfalfa events as an empirical approach to bypass the random transgenic silencing and for the identification of an event with optimal transgene expression. In this focus article, we report the complete sequence of pPZP200BAR and the extremely high efficiency of this binary vector in alfalfa transformation, opening the way for rapid and inexpensive production of transgenic events for alfalfa improvement public programs.